Integrasi Nilai Pancasila Dalam Praktek Hukum Internasional Menanggapi Agresi Israel Terhadap Palestina - Pratama, Karisma Bintang (Fakultas Hukum Universitas Islam Indonesia, 2025)
This article discusses the integration of Pancasila values into international law as the basis for Indonesia's diplomatic practice regarding Israel's acts of aggression against Palestine. Israel's aggression against Palestine is seen as a gross violation of human rights, especially for Palestinians. Israel's human rights violations against Palestinians constitute a deprivation of the rights of others, especially the right to live safely and decently. The conflict between Israel and Palestine has not yet found a bright spot of peace and has claimed many lives to date. The purpose of this study is to analyze Indonesia's role and contribution to influencing international legal practice through the application of the integration of Pancasila values in response to Israel's acts of aggression against Palestine. To analyze this problem, normative juridical research methods are used with a statute approach, a conceptual approach, and a case approach. The study concludes that Israel has violated humanitarian principles and has been ruled by the International Court of Justice that Israel's occupation of Palestine is illegal. Furthermore, it can be conveyed that Indonesia with the integration of Pancasila values has been able to provide a significant boost in influencing the construction of international law, especially in forming international agreements and bilateral or multilateral cooperation. Pancasila is the foundation for Indonesia diplomats to promote and defend national interests, as well as uphold universal values embraced by the international community, including in the case of Israel's aggression against Palestine.